Influence of chitin nanocrystals on the dielectric behaviour and conductivity of chitosan-based bionanocomposites. (20th October 2018) - Salaberría, A.M.; Teruel-Juanes, R.; Badia, J.D.; Fernandes, S.C.M.; Sáenz de Juano-Arbona, V.; Labidi, J.; Ribes-Greus, A.
Abstract: A series of bionanocomposite films based on chitosan, reinforced with chitin nanocrystals, were developed, and assessed in terms of dielectric behaviour and conductivity by using an experimental methodology that allows avoiding the conductivity contribution and the exclusion of contact and interfacial polarization effects. The dielectric relaxations at low and high frequency and temperatures were modeled by Havriliak-Negami functions. Below the glass transition temperature (Tg), the γ and β relaxations were observed, which were related to intramolecular and non-cooperative segmental movements. At higher temperatures, an intermolecular and cooperative macromolecular movement, related to the glass transition, gave rise to α-relaxation. In addition, two over-Tg ρ I and ρ II relaxations were found, which were related to the displacement of dipoles in the disordered structure of bionanocomposites. The addition of chitin nanocrystals did not affect the apparent activation energy Ea of the γ -relaxation. However, it decreased the Ea of the β -relaxation and increased the free volume at temperatures in the vicinities of the α-relaxation. Finally, the electric conductivity of the bionanocomposites was lower than that of neat chitosan and chitin due to the interaction between the OH and NH2 groups that reduced the ionic mobility, along with the increase of free volume, with the subsequent separation of phases.